The p60 recombinant antigen of Listeria monocytogenes - Mukantayev , K.N.; Begaliyeva , A.; Inirbay , B.; Raiymbek , G.; Kazyken , D.; Segizbayeva , G.Zh.; Shevtsov , A.B.; Mukanov , K.K. (Eurasian Journal of Applied Biotechnology, 2015)
Improvements in immunological methods for the diagnosis of listeriosis are important in the prevention of foodborne diseases. Currently, an important diagnostic antigen of Listeria monocytogenes is the p60 protein. The 625-bp-long central part of the p60 gene was synthesized with polymerase chain reaction. In this study, genomic DNA from strains of L. monocytogenes that was isolated in the Republic of Kazakhstan was used. The gene had structural features that were characteristic of the p60 gene of Listeria. Six codons of the histidine amino acid were added. The synthesized gene was cloned in a pET32 expression plasmid, which was transformed into Escherichia coli, strain BL21. As a result of the heterologous expression, a protein with a molecular weight of 40 kDa, which corresponded to the expected mass of the recombinant antigen, was obtained. Monoclonal antibodies against 6xHis-Tag reacted to the 40-kDa protein. Results from an enzyme-linked immunosorbent analysis showed specific reactions between the recombinant antigen and specific polyclonal antibodies, which were obtained by the immunization of BALB/c mice with the AUF vaccine against animal listeriosis. These results suggest that the p60 recombinant protein that was obtained can be used in the diagnostics of listeriosis.